ON’IN DATSURAKU IN THE TRANSLATION OF PLACE NAMES IN THE GAME FATE/GRAND ORDER - Darussalam, Daffa Setia; Ali, Mohammad (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This study aims to describe the process of phoneme change in place name translation, based on Suzuki's theory (in Nasution, 2017). The data used in this study are place names from two game versions with different languages, namely Japanese and English, entitled Fate/Grand Order. This research uses a qualitative descriptive method. The results of this study are from 10 data that have been analyzed, resulting in 18 vowel phoneme deletions, which are dominated by the vowel phoneme /u/ as much as 61%, followed by the vowel phonemes /o/, /i/ and /a/. Then, there is 1 consonant phoneme deletion which is dominated by the consonant phoneme /t/.